Construction Professionals’ Awareness of Automation and Robotics in South Africa - Mbhalati, Kurisani Luther (University of the Witwatersrand, Johannesburg, 2024)
In South Africa, the construction sector, which accounts for approximately 3% of the GDP, is essential for economic growth but struggles with issues such as falling productivity, quality concerns, and safety risks. The adoption of robotics and automation could address these challenges, offering more reliable and precise quality, boosting productivity, cutting costs, and increasing safety by automating dangerous tasks. This cross-sectional study aimed at assessing the awareness of automation and robotics among South African construction professionals through a quantitative survey. Additionally, the research sought to capture the professionals' opinions on the benefits these technologies could offer to construction projects and identify the barriers to their wider adoption as perceived by these professionals. Findings indicated a varied level of awareness among construction professionals, with high familiarity in technologies like Computer-Aided Design (CAD) and lower awareness in emerging technologies such as Virtual Reality (VR). Moreover, the professionals acknowledged the benefits of adopting these technologies, notably highlighting increased productivity and safety as key benefits. They also identified significant barriers to adoption, citing high acquisition costs and socio-economic concerns over job displacement as major obstacles, particularly in a context of high unemployment rates. Considering the construction industry's role in economic growth and recognizing the dip in productivity, alongside the industry's reluctance towards innovation, the study recommends focused educational initiatives and promotional activities for robotics and automation. It further stresses the need for policy changes to ensure the safe and efficient implementation of these technologies. Moreover, from a governmental standpoint, the study suggests providing incentives to businesses to encourage the adoption of robotics and automation in the construction industry
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Robotics; Robotics; Automation; Construction; Awareness; Barriers; Benefits; SDG-8: Decent work and economic growth